“The Learning Process Is Mutual”: Connecting Student Teachers and In-Service Teachers in Intercultural Virtual Exchange - Sina Werner; Robert O’Dowd (Social Sciences)
This article reports on a case study where students of Initial Teacher Education in Spain and Germany collaborated with in-service teachers from around Europe on the theme of Foreign Language materials development. It examines to what extent engagement in this model of virtual exchange contributes to student teachers’ and in-service teachers’ intercultural and didactic competence development. The study also explores how students’ perspectives on teaching foreign languages and their future profession change through collaboration with in-service teachers and how the student teachers’ and in-service teachers’ roles unfold in this type of collaboration. It is based on a qualitative content analysis of focus-group interviews, learning portfolios, recordings of online meetings, and questionnaires with open-ended questions. The findings indicate that this type of collaboration can reduce the gap between theory and practice: through the classroom experiences of in-service teachers, student teachers gain intercultural, professional knowledge and motivation, while in-service teachers gain knowledge about recent methodologies and technology through the alternative perspective of student teachers. We use the findings of our study to make recommendations on how other teacher trainers can use this Virtual Exchange model in the classroom.